Diffusion of Nd in hcp Mg and interdiffusion coefficients in Mg–Nd system. (November 2015) - Paliwal, Manas; Das, Sazol K.; Kim, Junghwan; Jung, In-Ho
Graphical abstract: Abstract: Diffusion couple experiments for Mg–Nd system were performed to investigate the Nd diffusion in Mg solid solution and the interdiffusivities of intermediate phases. Experiments were conducted at 460, 480 and 500 °C for 3, 4 and 3 days respectively. Phase diagram data obtained from the diffusion couple experiments are consistent with previous experimental data and thermodynamic modeling. Impurity diffusion coefficient of Nd in Mg solid solution is almost three times of Gd and Y but lower than that of Al and Zn.